2018
DOI: 10.1530/ec-17-0308
|View full text |Cite
|
Sign up to set email alerts
|

Serum and urine vitamin D metabolite analysis in early preeclampsia

Abstract: Vitamin D deficiency is common in pregnant women and may contribute to adverse events in pregnancy such as preeclampsia (PET). To date, studies of vitamin D and PET have focused primarily on serum concentrations vitamin D, 25-hydroxyvitamin D3 (25(OH)D3) later in pregnancy. The aim here was to determine whether a more comprehensive analysis of vitamin D metabolites earlier in pregnancy could provide predictors of PET. Using samples from the SCOPE pregnancy cohort, multiple vitamin D metabolites were quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…The observation that 25OHD levels during the first trimester in healthy pregnant women are lower than those of non-pregnant women has previously been described ( 19 , 20 , 21 , 22 ). Holmes et al found that serum 25OHD levels were lower in pregnant women ( n = 98) compared to non-pregnant women ( n = 38) ( P < 0.0001) ( 18 ).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The observation that 25OHD levels during the first trimester in healthy pregnant women are lower than those of non-pregnant women has previously been described ( 19 , 20 , 21 , 22 ). Holmes et al found that serum 25OHD levels were lower in pregnant women ( n = 98) compared to non-pregnant women ( n = 38) ( P < 0.0001) ( 18 ).…”
Section: Discussionmentioning
confidence: 66%
“…Even, Khan et al have found a higher prevalence of vitamin D deficiency in pregnant women ( n = 36) than in non-pregnant women ( n = 35) despite being matched by age and same area of residence ( 20 ). Also, Tamblyn et al found lower levels of 25OHD in healthy pregnant women ( n = 25) than in non-pregnant women ( n = 9) ( 21 ). Moreover, Gellert et al showed that 25OHD levels were lower in pregnant women in all trimesters of pregnancy ( n = 429) compared to non-pregnant women ( n = 429) and found an odds ratio (OR) of 13 to develop vitamin D deficiency in pregnant women compared to non-pregnant women ( n = 26) ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The placenta has however been suggested to be a major site of CYP24A1 expression and therefore catabolism of 1,25(OH)2D and 25(OH)D and is potentially a source of circulating 24,25(OH)2D. Altered placental vitamin D metabolism and plasma concentrations of vitamin D metabolites have been reported in women with pre-eclampsia (25). Serum 1,25(OH)2D concentrations were above published reference range in non-pregnant adults (36-144 pmol/L ( 16)) in the majority of cases and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D, its metabolites and VDBP have been detected and measured in a wide range of human tissues and bodily fluids, other than plasma. These include breast milk, urine, semen, saliva, cerebrospinal and synovial fluid, skin and muscle biopsies and hair samples [89][90][91][92][93][94]. The collection of such samples may provide benefits, such as ease of sample collection and avoidance of invasive sampling methods or for the investigation of organ-specific aspects of vitamin D metabolism and function.…”
Section: Measurement Of Vitamin D Metabolites In Tissues and Bodily Fmentioning
confidence: 99%